REPETISI DAN KOLOKASI DALAM TAJUK RENCANA SURAT KABAR KOMPAS - Lestari, Septi; Charlina, Charlina; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study aimed to describe the use of repetition and collocation in an editorial the newspaper Kompas. This research uses descriptive method. The study concluded that the use of repetition in Kompas newspaper editorial amounted to 128 data. The use of full reps edition March 11, 2015 until 11 April 2015 amounted to 40 (13 22 word phrase and clause 5). Repetition with other forms of editorial Kompas newspaper March 11, 2015 until 11 April 2015 amounted to 30 data. Reps with the replacement in an editorial the newspaper Kompas March 11, 2015 until 11 April 2015 amounted to 57 the data (48 words and phrases 9). Reps with hyponymy and hypernymy in Kompas newspaper editorial edition March 11, 2015 until 11 April 2015 amounted to 1 data. The use of collocation in an editorial the newspaper Kompas March 11, 2015 until 11 April 2015 amounted to 37 data.Keywords: Repetition, collocation, editorials, newspaper Kompas